A combined approach of VNTR and MLST analysis: Improvement of molecular typing of argentinean isolates of Leptospira interrogans - Caimi, Karina Cynthia (2012)
Leptospirosis is an emerging infectious disease that has been identified as both a human and animal health problem worldwide. Regular outbreaks associated with specific risk factors have been reported in Argentina. However, there are no available data concerning the genetic population level for this pathogen. Therefore, the aim of this work was to describe the genetic diversity of Leptospira interrogans through the application of two molecular typing strategies: variable number of tandem repeats (VNTR) and multilocus sequence typing (MLST). For this purpose, seven reference strains and 18 non-epidemiologically related isolates from diverse hosts and Argentinean regions were analysed. Among them, nine genotypes and seven sequence types (STs), including three unreported STs, were described using VNTR and MLST, respectively. eBURST analysis demonstrated that ST37 was the most frequent and founder genotype of a clonal complex (CCs) containing STN1 and STN3, suggesting the importance of studying the serovars belonging to this CC in Argentina. The data from maximum parsimony analysis, which combined both techniques, achieved intra-serovar discrimination, surmounted microscopic agglutination test discrepancies and increased the discriminatory power of each technique applied separately. This study is the first to combine both strategies for L. interrogans typing to generate a more comprehensive molecular genotyping of isolates from Argentina in a global context.